A Comment on the "Strategic Complexity and the Value of Thinking by D. Gill and V. Prowse (2023)" - Francesco Fallucchi; Andrea Marietta Leina; Rui Silva; Theodore L. Turocy (Institute for Replication (I4R), 2024)
Gill and Prowse (2023) study response times using a repeated p-beauty contest (p = 0.7). Looking at between-subject variation in response times, they found that subjects who think for longer, on average, win more rounds and choose lower numbers. When comparing average response times and level-k behavior, they observed that higher k types think for longer. In general, we are able to reproduce their findings, despite a minor coding error and some missing information. We test the robustness of their results by comparing average and median response times and choices, separating the sample into quick and slow respondents, including additional controls, and different estimation parameters. We do not find differences between choices between slow and quick respondents, somewhat contradicting their conclusions. Moreover, most subjects played faster as the game was repeated. The remaining results are robust to the inclusion of cohort effects and different parameter specifications in their regressions.
Keywords: C71; C92; 330; beauty contest; response times; level-k; strategic complexity